Nanometer layered double hydroxide conformally mineralized porous membrane, and preparation method and application thereof
Patent Information
- Application Number
- CN202611277034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-20
AI Technical Summary
这些苛刻的条件极易导致聚合物膜发生溶胀、水解、降解等损伤,从而削弱膜的整体性能
(1)本发明通过在复杂多孔基底表面及孔道构筑共形无定形Al2O3前驱层,并通过矿化孵育诱导界面处LDH原位生长,可在三维孔道内实现纳米尺度LDH矿化涂层的连续、均匀构筑。通过精确控制前驱层厚度与矿化条件,可有效避免对产生孔道堵塞的风险。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane separation materials technology, and in particular to a nano-layered double hydroxide conformal mineralized porous membrane, its preparation method, and its application. Background Technology
[0002] Constructing inorganic mineral coatings on porous membrane surfaces is an important method for functionalizing interfaces in the field of membrane separation technology. Introducing mineral coatings such as metal oxides / hydroxides allows for the synergistic regulation of membrane surface wettability by utilizing surface hydroxyl groups and micro / nano rough structures, and also enables catalytic and other interfacial reaction functions when transition metal sites are integrated. Among these, layered double hydroxides (LDHs) have attracted considerable attention due to their unique physicochemical properties. LDHs are a class of layered inorganic materials composed of divalent / trivalent metal cations, and can be expressed using the general formula... It means that M 2+ It is a divalent metal cation, M 3+ A is a trivalent metal cation. n- It is an anion exchangeable layer. Its advantages as a polymer film mineral coating are: (1) The large number of hydroxyl groups in the layers and between the layers endow it with intrinsic hydrophilicity, which is beneficial to resist the adsorption of organic pollutants; (2) During in-situ growth, it will form a vertically interlaced nanosheet array topology, which is beneficial to constructing a stable Cassie–Baxter superwetting interface; (3) The bimetallic structure of the main layer makes it easy to flexibly introduce transition metal ions (such as Co). 2+ Ni 2+ This endows membranes with catalytic activity.
[0003] Generally speaking, the following key technical requirements must be met for inorganic mineral coating modification on the surface of porous polymer membranes: (1) Strong interfacial bonding: The mineral coating must be firmly bonded to the polymer substrate to resist long-term fluid erosion; (2) Good conformal coverage: The coating must grow uniformly along the complex three-dimensional pore structure of the membrane to maximize the exposure of functional sites; (3) Structural size matching: The mineral size must match the pore size of the membrane (usually submicron) to avoid pore blockage; (4) Mild reaction conditions: The preparation process must avoid extreme conditions to protect the structural integrity of the polymer substrate. In existing technologies, the construction of LDH coatings on polymer porous membranes mainly employs hydrothermal methods or (hydrolysis) coprecipitation methods. These traditional methods have the following inherent technical limitations, making it difficult to simultaneously meet all the above requirements: First, uneven mass transfer occurs. The driving force of the reaction originates from the thermodynamic supersaturation of a homogeneous monophase solution. When applied to porous membranes, reactant concentration and pH gradients inevitably occur inside and outside the membrane and at different depths of the pores, leading to uneven mass transfer. This causes minerals to preferentially grow on the outer surface of the membrane and at the pore openings, resulting in disordered and rapid deposition, while nucleation at deeper pores is slow or even impossible. Ultimately, LDH sheets accumulate on the outer surface of the membrane and at the pore openings, often reaching micrometer-scale sizes, far exceeding the submicrometer pore size of the membrane, thus causing severe pore blockage. Second, the reaction conditions are harsh. Hydrothermal methods typically require high temperature (>100 °C) and high pressure environments; while coprecipitation methods are based on slow ion hydrolysis coprecipitation, with reaction times reaching tens of hours. Both methods are usually carried out under strongly alkaline conditions (pH 10-12) to promote precipitation. These harsh conditions can easily cause damage to the polymer membrane, such as swelling, hydrolysis, and degradation, thereby weakening the overall performance of the membrane.
[0004] In summary, developing a conformal, controllable, and mild preparation method for nanoscale LDH coatings on complex substrates such as polymer porous membranes has significant application value. Summary of the Invention
[0005] This invention provides a conformal mineralized porous membrane of layered hydrogen hydroxide (LDH) and its preparation method, which enables the conformal, controllable and mild preparation of nanoscale LDH coatings on complex substrates such as polymer porous membranes.
[0006] The technical solution of the present invention is as follows: A method for preparing a nanolayered double hydroxide conformal mineralized porous membrane includes the following steps: (1) Deposit an amorphous Al2O3 precursor layer on the clean and dry porous substrate membrane surface and within the pores; (2) Place the porous substrate membrane loaded with an amorphous Al2O3 precursor layer in a container containing divalent transition metal ions M 2+ The porous base membrane was incubated in a mineralization solution to mineralize it. (3) The mineralized porous base membrane is washed and dried to obtain the final product.
[0007] The core idea of this invention is to construct a nanoscale-thick amorphous metal oxide precursor layer on the surface and within the pores of a porous substrate membrane, thereby transferring the mineralization source and reaction space from the bulk solution and confining them to the membrane-liquid interface, thus achieving a shift in the mineralization process from bulk-dominated to interface-dominated. Specifically, a conformal amorphous Al2O3 thin layer is first deposited on the surface and within the pores of the polymer porous membrane, serving as the Al required for LDH growth. 3+ Interfacial precursor sources of components: On the one hand, the precursor layer releases Al through slow release. 3+ Species provide a source of trivalent metals for LDH laminations, avoiding the addition of large amounts of Al to the bulk phase. 3+ Salts induce disordered nucleation in the solution; on the other hand, the amorphous layer slowly hydrates at the interface under aqueous conditions and transforms into hydroxides / hydroxyoxides, consuming protons and increasing the local pH. This creates a localized alkaline chemical environment suitable for LDH nucleation and growth in situ at the membrane-liquid interface, eliminating the need to increase the reaction temperature or adjust the overall solution with strong alkali, significantly reducing the risk of damage to the polymer substrate. Subsequently, the precursor layer is exposed to a solution containing divalent metal ions M 2+ In an aqueous solution, make M 2+ In the interface neighborhood and the released Al 3+ Species and OH - Synergistic nucleation and directional growth of LDH nanosheets along the membrane surface and pore inner walls. This is achieved by using Al... 3+ Species release, pH elevation and M 2+ The coordination nucleation process is confined to the membrane-liquid interface. This invention enables the controllable and conformal growth of LDH nanosheets on the surface and inside the pores of porous membranes under mild conditions.
[0008] Preferably, the porous substrate membrane is at least one of polyvinylidene fluoride (PVDF) porous membrane, polyethersulfone (PES) porous membrane, polypropylene (PP) porous membrane, polytetrafluoroethylene (PTFE) porous membrane, carbon cloth, and carbon paper.
[0009] Porous basement membranes can be cleaned using organic solvents, water washing, or ultrasonic cleaning to remove surface oil, additives, and particulate impurities. The drying temperature is generally room temperature to 60 ℃, and the time is 0.5 h to 2 h to obtain a clean porous basement membrane.
[0010] Preferably, in step (1), an amorphous Al2O3 precursor layer is deposited on the surface and within the pores of the porous base membrane by atomic layer deposition (ALD), sol-gel method or chemical vapor deposition (CVD).
[0011] The most preferred method is to deposit an amorphous Al2O3 precursor layer on the surface and within the pores of a porous substrate membrane using atomic layer deposition, including but not limited to uniform deposition and single-sided deposition.
[0012] The amorphous Al2O3 precursor layer obtained by atomic layer deposition is highly conformal and has a controllable thickness. This allows the nucleation and growth space of LDH to be confined to the interface region near the substrate surface, enabling universal mineralization modification of different types of substrate interfaces.
[0013] In a further preferred embodiment, high-purity nitrogen is used as the carrier gas and purge gas, and trimethylaluminum and deionized water are used as precursors for atomic layer deposition.
[0014] More preferably, the atomic layer deposition temperature is 50–120 °C, and more preferably 80–100 °C.
[0015] The number of atomic layer deposition cycles is adjusted according to the target thickness and substrate pore size. The thickness of the amorphous Al2O3 precursor layer is designed to form a continuous conformal precursor layer within the pores while avoiding significant pore blockage after conversion.
[0016] Preferably, the thickness of the amorphous Al2O3 precursor layer is 2–15 nm, and more preferably 5–10 nm.
[0017] In other embodiments, in applications where conformity requirements are relatively low, the amorphous Al2O3 precursor layer can also be constructed by methods such as sol-gel coating and chemical vapor deposition. As long as the resulting oxide layer is amorphous or weakly crystalline and can be partially hydrated in an aqueous phase and release metal cations, it can be used for subsequent LDH mineralization growth.
[0018] Preferably, the mineralization solution contains divalent transition metal ions M. 2+ The aqueous solution of M; 2+ For Co 2+ And / or Ni 2+ .
[0019] In the mineralized solution, M 2+ The molar concentration is 0.01–0.1 mol·L⁻¹. -1 The preferred concentration is 0.05–0.1 mol·L⁻¹. -1 .
[0020] Depending on the needs, types such as chloride, carbonate, nitrate, and sulfate can be selected to control the final type of LDH intercalation anion.
[0021] In step (2), the incubation involves immersing a porous substrate membrane loaded with an amorphous Al2O3 precursor layer completely or partially in a mineralization solution and maintaining it at a certain temperature for a certain time, so that the amorphous Al2O3 precursor layer undergoes hydration transformation at the surface and the LDH undergoes in-situ nucleation and growth.
[0022] Preferably, in step (2), the incubation temperature is 15–25 °C and the incubation time is 1–8 h.
[0023] In step (3), the washing process involves taking the incubated porous base membrane out of the mineralization solution and rinsing or soaking it with deionized water to remove residual unreacted metal ions, free salts and loose deposits.
[0024] Preferably, in step (3), the drying temperature is 25–60 °C and the drying time is 1–6 h.
[0025] After washing and drying, a modified material with LDH nano-coating conformally loaded on the surface and pores of a porous base membrane is obtained.
[0026] The present invention also provides a nano-layered double hydroxide conformal mineralized porous membrane prepared by the above preparation method.
[0027] The present invention also provides the application of the aforementioned nanolayered double hydroxide conformal mineralized porous membrane in water treatment.
[0028] Preferably, the water treatment includes one or more of the following: oil-water separation, emulsion separation, membrane fouling catalytic self-cleaning, and catalytic degradation of pollutants.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention constructs a conformal amorphous Al2O3 precursor layer on the surface and pores of a complex porous substrate, and induces in-situ growth of LDH at the interface through mineralization incubation, thereby achieving continuous and uniform construction of nanoscale LDH mineralized coating within three-dimensional pores. By precisely controlling the thickness of the precursor layer and the mineralization conditions, the risk of pore blockage can be effectively avoided.
[0030] (2) The present invention can complete the interface mineralization process under mild conditions at room temperature, without the need for overall strong alkali treatment or high temperature treatment, and is friendly to various polymer porous substrates. Relying on the unified mineralization interface provided by the ALD precursor layer, the method has weak dependence on substrate material and surface chemistry, and is applicable to a variety of polymers and inorganic substrates, with strong substrate applicability.
[0031] (3) Thanks to the high hydrophilicity of the LDH coating itself, the present invention can adjust the original hydrophobic or moderately hydrophilic substrate surface to a superhydrophilic state, and combined with the rough structure of LDH nanosheets, further realize underwater superoleophobic wetting behavior, giving the substrate film excellent anti-oil stain performance.
[0032] (4) In this invention, the LDH plate can introduce transition metal components with highly dispersed layered coordination environment during the mineralization process, integrate uniformly distributed transition metal catalytic sites, realize the integrated construction of membrane separation and interface catalysis functions, and provide an efficient and scalable technical path for developing multifunctional membrane materials and interfaces that combine functions such as oil-water separation, emulsion separation and other pollutant separation and catalysis (such as catalytic degradation of pollutants, coupled reaction-separation process, etc.). Attached Figure Description
[0033] Figure 1 To illustrate the surface morphology of LDH coatings constructed on different substrates, (a) and (c) show the surface morphology of the PVDF porous substrate before mineralization; (b) and (d) show the surface morphology of the CoAl LDH / PVDF and NiAl LDH / PVDF coatings, respectively; (e) and (g) show the surface morphology of the hydrophilic carbon fiber (CF) and hydrophobic carbon paper (CP) substrates before mineralization; and (f) and (h) show the surface morphology of the corresponding substrates after mineralization in cobalt ion solution. Figure 2 The cross-sectional morphology of the LDH coating constructed on the PVDF porous substrate is shown in (a) CoAl LDH / PVDF; (b) NiAl LDH / PVDF. Figure 3 To demonstrate the adjustability of PVDF porous substrate pore size and coating thickness during the mineralization process of this invention, (a) the average pore size of the original PVDF, Al2O3-PVDF deposited with Al2O3 via ALD, and CoAl LDH / PVDF at different mineralization times (0.5 h, 1 h, 1.5 h, 2 h); (b) the relationship between the corresponding coating thickness and mineralization time. Figure 4 To assess the wettability and self-cleaning properties of mineralized membranes, (a) a comparison of the static water contact angles of the original PVDF and CoAl LDH / PVDF membranes, (b) the contact angle of the CoAl LDH / PVDF membrane with crude oil droplets underwater is ~172.6°, and (c) the self-cleaning properties of the membranes. Figure 5This study characterizes the antifouling and self-cleaning properties and Fenton-like catalytic activity of mineralized membranes in crude oil-water emulsion separation. Specifically: (a) flux changes of the original PVDF membrane and the CoAl-LDH / PVDF mineralized membrane during three consecutive crude oil-water emulsion filtration cycles, and a comparison of membrane surface states before and after cleaning with 1.5 mM PMS aqueous solution; (b) oil rejection rate and total organic carbon (TOC) content of the filtrate of the CoAl-LDH / PVDF mineralized membrane during the cyclic separation process, showing the appearance of the original emulsion and the filtrate after separation; (c) in-situ EPR spectra obtained using TEMP and DMPO as spin trapping agents, used to characterize the EPR generated during PMS activation. 1 O2, ·OH, and SO4· - Active species. Detailed Implementation
[0034] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not limit it in any way.
[0035] Example 1 (1) A commercial PVDF microfiltration membrane (average pore size of about 0.22 μm and thickness of about 100 μm) was selected as the substrate. The membrane was rinsed in anhydrous ethanol and deionized water for 10 min each. After being removed, it was dried in an oven at 40 ℃ for 0.5 h to obtain a clean and completely dry PVDF substrate.
[0036] (2) The substrate was placed in a vertical atomic layer deposition (ALD) apparatus. High-purity nitrogen was used as the carrier gas and purge gas at a flow rate of 50–80 sccm. The chamber was evacuated to approximately 50 Pa and then heated to 100 °C under a nitrogen atmosphere. Trimethylaluminum (TMA) and deionized water were then used as precursors for deposition. The program for a single ALD cycle was set as follows: TMA pulse 0.3 s, residence time 5 s, nitrogen purge 15 s, water pulse 0.09 s, residence time 7 s, nitrogen purge 15 s, for a total of 100 cycles. This yielded an amorphous Al2O3 precursor layer with an equivalent thickness of approximately 10 nm. After the reaction, a nitrogen clean was performed on the ALD system for approximately 10 cycles. The membrane was then removed and allowed to cool naturally to room temperature for later use.
[0037] (3) Weigh out Co(Cl)2·6H2O and dissolve it in deionized water to prepare a solution of 0.05 mol·L -1 Co 2+ After the mineralization solution is stirred until completely dissolved at room temperature, the Al2O3 / PVDF membrane is completely immersed in the solution and incubated at room temperature for 2 hours.
[0038] (4) After the incubation is completed, the membrane is taken out, rinsed repeatedly with a large amount of deionized water, and then placed in water and washed on a shaker 3 times. The water is changed every 0.5 h. Then it is dried at 40 ℃ for 2 h to obtain CoAl-LDH nano-coated mineralized modified PVDF membrane (CoAl LDH / PVDF).
[0039] Example 2 (1) A commercial PVDF microfiltration membrane (average pore size of about 0.22 μm and thickness of about 100 μm) was selected as the substrate. The membrane was rinsed in anhydrous ethanol and deionized water for 10 min each. After being removed, it was dried in an oven at 40 ℃ for 0.5 h to obtain a clean and completely dry PVDF substrate.
[0040] (2) The substrate was placed in a vertical atomic layer deposition (ALD) apparatus. High-purity nitrogen was used as the carrier gas and purge gas at a flow rate of 50–80 sccm. The chamber was evacuated to approximately 50 Pa and then heated to 80 °C under a nitrogen atmosphere. Trimethylaluminum (TMA) and deionized water were then used as precursors for deposition. The program for a single ALD cycle was set as follows: TMA pulse 0.05 s, residence time 5 s, nitrogen purge 30 s, water pulse 0.05 s, residence time 5 s, nitrogen purge 30 s, for a total of 100 cycles. This yielded an amorphous Al2O3 precursor layer with an equivalent thickness of approximately 10 nm. After the reaction, a nitrogen clean was performed on the ALD system for approximately 10 cycles. The membrane was then removed and allowed to cool naturally to room temperature for later use.
[0041] (3) Weigh out Ni(Cl)2·6H2O and dissolve it in deionized water to prepare a solution of 0.1 mol·L -1 Co 2+ After the mineralization solution is stirred until completely dissolved at room temperature, the Al2O3 / PVDF membrane is completely immersed in the solution and incubated at room temperature for 2 hours.
[0042] (4) After the incubation is completed, the membrane is taken out, rinsed repeatedly with a large amount of deionized water, and then placed in water and washed on a shaker 3 times. The water is changed every 0.5 h. Then it is dried at 40 ℃ for 2 h to obtain NiAlLDH nano-coated mineralized modified PVDF membrane (NiAl LDH / PVDF).
[0043] Example 2-3 In Examples 2 and 3, the PVDF microfiltration membrane in Example 1 was replaced with hydrophilic carbon fiber (CF) and hydrophobic carbon paper (CP), respectively, to obtain CoAl LDH / CF and CoAl LDH / CP.
[0044] Example 4 (1) A commercial polyethersulfone (PES) ultrafiltration membrane (with a molecular weight cutoff of about 50 kDa and a thickness of about 120 μm) was selected as the substrate. The membrane was rinsed in isopropanol and deionized water for 10 min each. After being removed, it was dried in an oven at 50 °C for 0.5 h to obtain a clean and completely dry PES substrate.
[0045] (2) The substrate was placed in a vertical atomic layer deposition (ALD) apparatus. High-purity nitrogen was used as the carrier gas and purge gas at a flow rate of 50-80 sccm. The chamber was evacuated to about 50 Pa and then heated to 80 °C in a nitrogen atmosphere. Trimethylaluminum (TMA) and deionized water were used as precursors for deposition. The program for a single ALD cycle was set as follows: TMA pulse 0.5 s, retention time 7 s, nitrogen purge 15 s, water pulse 0.15 s, retention time 7 s, nitrogen purge 15 s, and a total of 30 cycles were performed. An amorphous Al2O3 precursor layer with an equivalent thickness of about 3 nm was obtained. After the reaction was completed, a nitrogen clean was performed on the ALD system for about 10 cycles. The membrane was then removed and allowed to cool naturally to room temperature for later use.
[0046] (3) Weigh out NiSO4·6H2O and dissolve it in deionized water to prepare a solution of 0.08 mol·L -1 Ni 2+ After the mineralization solution is stirred until completely dissolved at room temperature, the Al2O3 / PES membrane is completely immersed in the solution and incubated at room temperature for 1 h.
[0047] (4) After the incubation is completed, the membrane is taken out, rinsed repeatedly with a large amount of deionized water, and then placed in water and washed on a shaker 3 times. The water is changed every 0.5 h. Then it is dried at 40 ℃ for 2 h to obtain NiAlLDH nano-coated mineralized modified PES membrane.
[0048] Example 5 (1) A commercial polytetrafluoroethylene (PTFE) microfiltration membrane (average pore size of about 0.22 μm and thickness of about 100 μm) was selected as the substrate. The membrane was rinsed in anhydrous ethanol and deionized water for 10 min each. After being removed, it was dried in an oven at 40 ℃ for 0.5 h to obtain a clean and completely dry PTFE substrate.
[0049] (2) The substrate was placed in a plasma treatment apparatus, with air as the working gas, and treated for 3 min at a power of 80 W and a chamber pressure of approximately 50 Pa to introduce a certain amount of polar functional groups onto the film surface, thereby improving surface wettability and precursor layer adhesion. Subsequently, aluminum isopropoxide was dissolved in anhydrous isopropanol at room temperature to prepare an Al-containing... 3+Concentration approximately 0.5 mol·L -1 The precursor solution was prepared, with a small amount of deionized water and acetylacetone added to adjust the hydrolysis and complexation rates. The plasma-activated PTFE membrane was immersed in this solution for 1 min using an dip-coating method, followed by a dip-coating process at approximately 1 mm / s. -1 The process involves allowing the material to stand at room temperature for 10 minutes to complete initial gelation, followed by heat treatment in an 80°C oven for 0.5 hours to remove organic residues. This process is repeated twice to achieve an amorphous alumina layer with an equivalent thickness of approximately 5 nm, resulting in a relatively uniform conformal coverage on the inner walls of the pores and the membrane surface.
[0050] (3) Subsequently, Co(NO3)2·6H2O and Ni(NO3)2·6H2O were weighed out and dissolved in deionized water to adjust the Co 2+ with Ni 2+ The molar ratio is 1:1, and the total metal ion concentration is 0.10 mol·L⁻¹. -1 A homogeneous Co / Ni composite mineralization solution was obtained by stirring at room temperature for 30 min. The PTFE membrane loaded with the amorphous alumina precursor layer was completely immersed in the solution and incubated at room temperature for 4 h.
[0051] (4) After the incubation is completed, the membrane is taken out, rinsed repeatedly with a large amount of deionized water, and then placed in water and washed on a shaker 3 times. The water is changed every 0.5 h. Then it is dried at 50 ℃ for 3 h to obtain (Co,Ni)AlLDH nano-coated mineralized modified PTFE membrane.
[0052] Combination Figures 1-5 It can be seen that the method proposed in this invention can realize the in-situ and conformal construction of LDH nanostructures on the surface of different types of porous substrates, and further endow the membrane material with good wetting control, separation and catalytic self-cleaning properties.
[0053] Figure 1 The results show that after mineralization treatment, dense and uniformly distributed layered nanostructures can be formed on the surfaces of different substrates such as PVDF membranes, carbon felt (CF), and carbon paper (CP), indicating that this method has good applicability to porous substrates with different compositions and morphologies. Meanwhile, both CoAl-LDH and NiAl-LDH can be formed on the surface of PVDF membranes, indicating that the mineralization method has a certain degree of controllability over the metal composition of LDH layers.
[0054] Figure 2The cross-sectional morphology further indicates that LDH mineralization does not only occur on the outer surface of the membrane, but can continue to grow along the internal pores and pore walls of the PVDF membrane, forming a mineralized layer covering the complex three-dimensional pore structure, indicating that the method has good in-pore permeation and conformal mineralization capabilities.
[0055] Figure 3 The results show that as the mineralization time increases, the thickness of the mineralized layer gradually increases, while the average pore size of the membrane gradually decreases from about 0.20 μm to about 0.08 μm. This demonstrates that by adjusting the mineralization time, the growth degree of the LDH mineralized layer and the membrane pore size can be effectively controlled. This allows for the formation of a continuous nanolayered structure while maintaining the porous connectivity of the membrane, thus achieving controllable adjustment of the porous membrane interface structure.
[0056] Original PVDF membranes and CoAl-LDH / PVDF mineralized membranes of the same size were taken separately. First, the membrane surfaces were pre-wetted with deionized water. Then, an appropriate amount of oil was applied to the membrane surface to ensure sufficient oil phase adhesion. Subsequently, the contaminated membrane sample was held with tweezers and slowly immersed in deionized water, with gentle agitation or inversion to ensure full contact between the water and the membrane surface. The desorption process of the oil on the membrane surface was recorded simultaneously. The results are as follows: Figure 4 As shown.
[0057] Figure 4 The results show that the water contact angle of the original PVDF membrane was approximately 53.7°, which decreased to nearly 0° after mineralization, exhibiting significant superhydrophilicity. Simultaneously, the oil contact angle of the mineralized membrane underwater reached approximately 172.6°, demonstrating excellent underwater superoleophobic properties. These results indicate that the LDH mineralization layer can significantly alter the wetting state of the membrane surface, forming an interface that facilitates aqueous wetting and inhibits oil droplet adhesion, providing a foundation for oil-containing system separation and oil contamination resistance.
[0058] Figure 5 This further verified the anti-fouling and catalytic self-cleaning capabilities of the mineralized membrane in the actual crude oil-water emulsion separation process.
[0059] The original PVDF membrane and the CoAl-LDH / PVDF mineralized membrane were installed in a membrane filtration unit, respectively. A prepared crude oil-water emulsion was used as the treatment solution, and filtration was performed for 60 min under the same operating pressure. Then, the feed solution was replaced with a 1.5 mM PMS aqueous solution to clean the membrane, ensuring sufficient contact between the PMS and the CoAl-LDH mineralized layer on the membrane surface and initiating a catalytic reaction. After cleaning, the membrane surface was rinsed with deionized water, and the crude oil emulsion was reintroduced for the next cycle of filtration. This process was repeated for three cycles, and the flux decline and recovery of the original PVDF membrane and the CoAl-LDH / PVDF membrane were compared in each cycle. The macroscopic fouling state of the membrane surface before and after PMS cleaning was also recorded. The results are as follows: Figure 5As shown in (a).
[0060] Electron paramagnetic resonance (EPR) was used to detect active species generated during the activation of PMS by CoAl-LDH / PVDF. A CoAl-LDH / PVDF mineralized film was added to a reaction system containing PMS, and different spin trapping agents were added for testing. TEMP was used as the trapping agent to detect singlet oxygen generated in the system. 1 O2); DMPO was used as a spin trapping agent to detect hydroxyl radicals (·OH) and sulfate radicals (SO4·). - Immediately after the mixtures of the various systems reacted, EPR tests were performed to determine the formation of active species based on the corresponding characteristic signals. Experimental results showed that the CoAl-LDH mineralization layer could activate PMS and produce… 1 O2, ·OH and SO4· - These reactive species provide the basis for the catalytic degradation and self-cleaning of organic pollutants on the membrane surface. Results are as follows... Figure 5 As shown in (c).
[0061] Compared to the original PVDF membrane, the CoAl-LDH / PVDF mineralized membrane maintained a higher flux during continuous filtration and achieved significant flux recovery and surface contaminant removal after PMS cleaning. Simultaneously, its oil rejection rate remained high throughout multiple cycles, and the filtrate TOC remained low, indicating that the mineralized membrane possesses stable oil-water separation capabilities. EPR testing further detected… 1 O2, ·OH, and SO4· - The presence of active species indicates that the CoAl-LDH mineralization layer can effectively activate PMS and degrade organic pollutants adsorbed on the membrane surface through in-situ catalytic oxidation, thereby achieving active self-cleaning after membrane fouling.
[0062] This invention employs a combined strategy of "metal oxide precursor layer + mild aqueous phase mineralization" to achieve controllable construction of a nanoscale, conformal LDH mineralization coating within the three-dimensional pores of a porous polymer membrane under mild conditions. Compared to common existing technologies such as hydrothermal methods, hydrolysis-precipitation methods, or methods involving organic modification with polydopamine followed by mineralization, this invention first conformally deposits an amorphous / weakly crystalline oxide precursor layer on the membrane surface and within the pores using low-temperature ALD, which can partially hydrate in the aqueous phase and release metal cations, thereby enabling the polymer membrane interface to acquire inorganic nucleation capabilities. Subsequently, under room temperature conditions without additional pH adjustment, a Co-containing... 2+ And / or Ni 2+The mineralization solution allows the metal cations released from the precursor layer to synergistically hydrolyze and assemble LDH sheets with divalent transition metal ions in the solution. In contrast, existing direct mineralization methods struggle to obtain conformally continuous nanoscale LDH coatings without significantly damaging the substrate or excessively clogging the pores. This invention, however, allows for precise control of LDH coverage and growth by adjusting the precursor layer thickness and mineralization conditions.
[0063] Compared with existing technologies, this invention, through the above-mentioned specific process steps and interface engineering design, elevates LDH mineralization from a process dependent on strong alkali precipitation and hydrothermal empirical conditions to a complete set of technical solutions with good reproducibility and universality on various polymer porous membranes, and with finely adjustable interface structures.
[0064] The embodiments described above provide a detailed explanation of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, and equivalent substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a nanolayered double hydroxide conformal mineralized porous membrane, characterized in that, Includes the following steps: (1) Deposit an amorphous Al2O3 precursor layer on the clean and dry porous substrate membrane surface and within the pores; (2) Place the porous substrate membrane loaded with an amorphous Al2O3 precursor layer in a container containing divalent transition metal ions M 2+ The porous base membrane was incubated in a mineralization solution to mineralize it. (3) The mineralized porous base membrane is washed and dried to obtain the final product.
2. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 1, characterized in that, The porous substrate membrane is at least one of polyvinylidene fluoride porous membrane, polyethersulfone porous membrane, polypropylene porous membrane, polytetrafluoroethylene porous membrane, carbon cloth, and carbon paper.
3. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 1, characterized in that, In step (1), an amorphous Al2O3 precursor layer is deposited on the surface and in the pores of a porous base membrane by atomic layer deposition, sol-gel method or chemical vapor deposition.
4. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 3, characterized in that, Amorphous Al2O3 precursor layers were deposited on the surface and within the pores of a porous substrate membrane using atomic layer deposition. High-purity nitrogen was used as the carrier gas and purge gas, and trimethylaluminum and deionized water were used as precursors for atomic layer deposition. The atomic layer deposition temperature is 50–120 °C.
5. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 1, characterized in that, The thickness of the amorphous Al2O3 precursor layer is 2–15 nm.
6. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 1, characterized in that, The mineralization solution contains divalent transition metal ions M. 2+ The aqueous solution of M; 2+ For Co 2+ And / or Ni 2+ .
7. The method for preparing the nanolayered double hydroxide conformal mineralized porous membrane according to claim 6, characterized in that, In the mineralized solution, M 2+ The molar concentration is 0.01–0.1 mol·L⁻¹. -1 .
8. The method for preparing a nanolayered double hydroxide conformal mineralized porous membrane according to claim 1 or 7, characterized in that, In step (2), the incubation temperature is 15–25 °C and the incubation time is 1–8 h.
9. A nano-layered double hydroxide conformal mineralized porous membrane prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the nanolayered double hydroxide conformal mineralized porous membrane according to claim 9 in water treatment.